First-principles prediction of high Curie temperature for ferromagnetic bcc-Co and bcc-FeCo alloys and its relevance to tunneling magnetoresistance - Lezaic, M.; Mavropoulos, Ph.; S. Blügel (APPLIED PHYSICS LETTERS, 2007)
{The authors determine from first principles the Curie temperature T-C for bulk Co in the hcp, fcc, bcc, and body-centered-tetragonal (bct) phases, for FeCo alloys, and for bcc and bct Fe. For bcc Co